Perception of readers towards the crime photographic images from the mainstream Malaysian newspaper in Kuala Terengganu / Farihan Zahari - Zahari, Farihan (2013)
Photographic image has trigged a huge phenomenon in all aspects of human life. Not only magazines, newspapers, billboards, the internet, even building are draped with photographic images. Recognizing the importance of images to the community, a study was carried out to identify the functions of the crime image displayed in press. In general, crime images are often displayed in the newspaper and it becomes an obligation to be showcased to the public. This function of this image is to provide a visual representation of the actual design to the community to be used as well as to be enlightened. However, the function of crime image portrayal in the press is questionable. This is on whether it is capable of delivering positive impacts or otherwise to newspaper readers, thus, this is the main objective to be achieved through this study. Three major newspapers were selected of Malay language newspaper Berita Harian, Utusan Malaysia and Harian Metro and violent crime pictures taken are effective from the year 2007-2010. For questions concerning these issues, two research approaches were employed through distribution of questionnaire and interview sessions. A total of 700 survey questionnaires were distributed and 10 respondents were interviewed: the newspaper editor; photographer, and; newspaper readers of various educational level of lecturers, students, and people with lower level of education. The purpose is to determine their perspective and find the differences in assessing the function of the crime image displayed on newspapers. From 700 survey distributed, only 404 surveys were answered. The results gained through the conducted questionnaire and interviews show that the crime image displayed in newspaper could provide positive impact on the reader. Although there are a few mentioned that it can give a negative impact and cause disturbing impacts to the reader, it does not represent the majority of the respondents. In summary, the collaboration between the editor and the photographer in the selection of crime images in the press are of utmost importance. Next, positive impact of this study has also proven that the effort the newspaper media in the social obligation to the community has been successful due to their self-consciousness when viewing such images. This study also proves that the image is one of the most effective medium in conveying message and information to the general public